Moderate altitude affects high intensity running performance in a collegiate women`s soccer game - Bohner, J. D.; Hoffman, J. R.; McCormack, W. P.; Scanlon, T. C.; Townsend, J. R.; Stout, J. R.; Fragala, M. S.; Fukuda, D. H. (Journal of Human Kinetics, 2015)
The effect of altitude on soccer game activity profiles was retrospectively examined in six NCAA Division I female soccer players. Comparisons were made between two matches played at sea level (SL) and one match played at a moderate altitude (1839 m). A 10-Hz global positioning system device was used to measure distance and velocity. The rate of total distance capacity (TDC) and high intensity running (HIR) as well as percent of time at HIR were evaluated. Significant differences were seen in the distance rate (120.55 ± 8.26 m·min-1 versus 105.77 ± 10.19 m·min-1) and the HIR rate (27.65 ± 9.25 m·min-1 versus 25.07 ± 7.66 m·min-1) between SL and altitude, respectively. The percent of time at HIR was not significantly different (p = 0.064), yet tended to be greater at SL (10.4 ± 3.3%) than at altitude (9.1 ± 2.2%). Results indicate that teams residing at SL and competing at a moderate altitude may have a reduced ability in distance covered and a high intensity run rate.